
展开全部
X-38=25
X+15=45
2X+5=32
4X=3+8
10X=4-3
12X=4/5
2X-X=2+3
48X=232-23
983-X-23=47
123-X=121
58X=43+12
12X=X-3
45X+12X=234
12.3X+17.5X=234
12X=12+23+34
480X=12X-12
154X=127-6
56%*X=23-13
123-X=45
145+65=X-1/3X
46X-24=15
23%*X=12+47
X+15=45
2X+5=32
4X=3+8
10X=4-3
12X=4/5
2X-X=2+3
48X=232-23
983-X-23=47
123-X=121
58X=43+12
12X=X-3
45X+12X=234
12.3X+17.5X=234
12X=12+23+34
480X=12X-12
154X=127-6
56%*X=23-13
123-X=45
145+65=X-1/3X
46X-24=15
23%*X=12+47
展开全部
7x-5/4=3/8
1/4-1/2=3/4
1/7X(2x+14)=4-2x
12X(2-2x)=4X+4
3y-4=y+3
4/10x-3=10x+2
3X(2x+1)=12
2X(200-15x)=70+25x
(3y-1/4)-1=(5y-7)/6
(3x-5)X3=(2x-1)X2
1/4-1/2=3/4
1/7X(2x+14)=4-2x
12X(2-2x)=4X+4
3y-4=y+3
4/10x-3=10x+2
3X(2x+1)=12
2X(200-15x)=70+25x
(3y-1/4)-1=(5y-7)/6
(3x-5)X3=(2x-1)X2
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询